Understanding the ecology and conservation of Jerdon’s sea snake (Hydrophis jerdonii Gray, 1849) - Prachi Hatkar; Rohit Khatua; Chinnasamy Ramesh (Journal of Marine Studies, 2026)
Hydrophis jerdonii (Jerdon’s sea snake) is a venomous and viviparous marine reptile widely distributed across the Indo-Pacific, including Indian waters. Despite its ecological importance, focused research on this species in India remains scarce. This review consolidates historical and contemporary literature (1849–2025) to assess the distribution, morphology, phylogeny, habitat, and conservation status of this species. A total of 75 publications were reviewed from databases such as Google Scholar, The Reptile Database, and the Biodiversity Heritage Library. Studies were categorised and analysed to quantify research emphasis across key ecological and biological parameters. Most studies (26%) addressed distribution, while only 3% focused on habitat ecology. The last confirmed live record of H. jerdonii in India dates to 2008 from the Mangalore coast, Karnataka, with subsequent findings limited to preserved specimens. Although listed as Least Concern by the IUCN, H. jerdonii faces increasing threats from bycatch and habitat degradation. The absence of recent field records underscores the urgent need for systematic surveys, ecological research, and molecular studies to reassess its current population status in Indian waters.